2021
DOI: 10.3390/polym13183055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Molecular Structure of TPU on the Cellular Structure of Nanocellular Polymers Based on PMMA/TPU Blends

Abstract: In this work, the effects of thermoplastic polyurethane (TPU) chemistry and concentration on the cellular structure of nanocellular polymers based on poly(methyl-methacrylate) (PMMA) are presented. Three grades of TPU with different fractions of hard segments (HS) (60%, 70%, and 80%) have been synthesized by the prepolymer method. Nanocellular polymers based on PMMA have been produced by gas dissolution foaming using TPU as a nucleating agent in different contents (0.5 wt%, 2 wt%, and 5 wt%). TPU characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It was observed that the density decreases linearly with an increase in the mass fraction of soft segments (see Figure 7 ). For comparison, the density of TPU depending on its chemical structure is in the range 1.1 g/ ... 1.21 g/ [ 48 ] (1.2 g/ [ 49 ], 1.11 g/ [ 50 ], ≈1.2 g/ [ 51 ]).…”
Section: Results and Discussionmentioning
confidence: 99%
“…It was observed that the density decreases linearly with an increase in the mass fraction of soft segments (see Figure 7 ). For comparison, the density of TPU depending on its chemical structure is in the range 1.1 g/ ... 1.21 g/ [ 48 ] (1.2 g/ [ 49 ], 1.11 g/ [ 50 ], ≈1.2 g/ [ 51 ]).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the blend, TPU will act as a crystallization nucleation agent [100,103] that will decrease the free energy barrier and helps in cell nucleation. Nucleation is the first step of the crystallization process [111].…”
Section: Thermal Properties Of Pla/tpu Blend Shape Memory Polymermentioning
confidence: 99%
“…A preliminary experiment reported the use of the method to achieve complex shapes endowed with morphological gradients, such as a 1:10 scale human femur. The authors adopted polystyrene as a model polymer and polycaprolactone for the femur, showing the versatility of the method for any foamable biomedical thermoplastic [ 70 , 71 , 72 , 73 , 74 ]. Most recently, the gas foaming method with time-varying boundary conditions has been coupled with additive manufacturing, providing additional versatility in terms of porosity architecture [ 75 ].…”
Section: Advanced Control Of Scaffold Architecturementioning
confidence: 99%